Feeding routines and feed quality on small-scale dairy farms in Baringo, Kenya - Möller, Maja (2018)
An increasing population together with a growing interest in consumption of animal proteins requires an intensified dairy production in Kenya. The aver-age milk production of 4.4 litres per cow and day is neither efficient enough nor reach the genetic capacity of the exotic dairy cattle used in the small-holder dairy sector. This study investigated feeding routines and feed quality in 31 small-holder dairy farms situated in the highlands (H) and lowlands (L) of Barin-go. Semi-structured interviews, observations and registrations of milk yield (MY), body weight (BW) and body condition score (BCS) were performed. The measured animal characteristics differed between the production envi-ronments highlands (408.1 kg BW; 6.9 kg MY; 2.4 BCS) and the lowlands (373.8 kg BW; 6.3 kg MY; 2.6 BCS). Feed samples of basal feeds, supple-mentary forages and commercial concentrates (Dairy meal) were collected for further analysis. The most commonly used basal feed was pasture fol-lowed by grass-mixtures mixed with crop residues, milling by-products and Dairy meal. The most used home-grown feeds were Napier grass, Rhodes grass hay, maize silage, maize stover, oats hay and Star grass hay. The feed analysis showed that two basal feeds had sufficient nutritional content to be used as solitary feed component to an average cow in the production envi-ronments based on measured and calculated average body weights and milk yields. There was a large variation in feed quality among the basal feeds and supplementary forages, the proportions of feed components in the mixtures varied depending on availability and season. The highest nutritional value, compared in crude protein (CP) and metabolisable energy (ME), among the basal feeds was in a mixture containing Columbus grass, Star grass hay, Na-pier grass, Lucerne, Dairy meal and wheat bran (14.4 % CP; 10.2 MJ ME/ kg DM). The lowest was seen in a mixture including Star- and Rhodes grass hay mixed with molasses to ferment in 24 hours (5.4 % CP; 7.3 MJ ME/ kg DM). A large variation was seen in the nutritive value of the Dairy meals (n=5), with one of the brands having a nutritional composition similar to a standard Swedish commercial concentrate (Lantmännen, 2017). Three samples had low levels of CP and high levels of calcium and magnesium suggesting alter-ations had been made to replace more expensive ingredients.